Pengaruh Struktur Modal, Profitabilitas Dan Likuiditas Terhadap Nilai Perusahaan - Dwi Artati; Akbar Tendi Sasongko (FEB UNWIKU PURWOKERTO, 2022)
In achieving company goals, human resources play a very important role. The organization will thrive if supported by loyal and highly committed employees, which is shown by their attitudes and behavior in the workplace. The purpose of this research is to find out the extent of OCB UMKM of Kabupaten Banyumas The approach used in this study is quantitative met hod with a mean score to measure employee OCB on obedience, loyalty and participation. The results of the study concluded that the three indicators used in the assessment show good average score. Of the three indicator values the smallest is the value of the participation indicator with 3.39. The lack of OCB values from participation indicator shows the degree of OCB held by UMKM Kabupaten Banyumas so that the institution can design trainings or workshops that are in accordance with employee needs so that employees can exhibit work behavior that exceeds standards